2019
DOI: 10.1080/17435390.2019.1675794
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in vitro digestion on gastrointestinal fate and uptake of silver nanoparticles with different surface modifications

Abstract: Nanomaterials, especially silver nanoparticles (AgNPs), are used in a broad range of products owing to their antimicrobial potential. Oral ingestion is considered as a main exposure route to AgNPs. This study aimed to investigate the impact of the biochemical conditions within the human digestive tract on the intestinal fate of AgNPs across an intestinal in vitro model of differentiated Caco-2/HT29-MTX cells. The co-culture model was exposed to different concentrations (250-2500 mg/L) of pristine and in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 55 publications
3
44
0
2
Order By: Relevance
“…The toxicity difference between digested and undigested silver nanoparticles was also studied. It was possible to verify how the undigested ones were mostly captured by the cellular model Caco-2/HT29-MTX [88]. In the study of Silvan et al [33], exposure of GSH-Ag NPs to epithelial cells (HT-29, Caco-2 and CCD-18) showed a dose-dependent cytotoxic effect and no significant cytotoxicity occurred until concentrations of 4.93 µg/mL.…”
Section: In Vitro Studies: Static and Dynamic Gut Simulators And Epitmentioning
confidence: 99%
“…The toxicity difference between digested and undigested silver nanoparticles was also studied. It was possible to verify how the undigested ones were mostly captured by the cellular model Caco-2/HT29-MTX [88]. In the study of Silvan et al [33], exposure of GSH-Ag NPs to epithelial cells (HT-29, Caco-2 and CCD-18) showed a dose-dependent cytotoxic effect and no significant cytotoxicity occurred until concentrations of 4.93 µg/mL.…”
Section: In Vitro Studies: Static and Dynamic Gut Simulators And Epitmentioning
confidence: 99%
“…Besides, the IC 50 values for cytotoxicity of the AgNPs in the mESCs were higher than what would be considered realistic in vivo concentrations as our results from the BeWo b30 transport experiments indicated low transport of AgNPs into the fetal compartment. Additionally, considering the oral route as one of the main exposure routes of the AgNPs, it is important to take into account also their very low transport across the intestinal barrier in vitro [14,56] and in vivo [15] which will consequently lower the concentrations of the AgNPs that might reach the fetus.…”
Section: Contribution Of Surface Chemistry Of Agnps On Transport Acromentioning
confidence: 99%
“…Previously, we studied the potential transport of AgNPs with different surface modifications across monolayers of intestinal epithelial cells in vitro [14]. We showed that in vitro simulated human digestion had a drastic effect on the dissolution of AgNPs, an effect that was surface coating dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Caco-2 cells were used at passage numbers 29-40, and HT29-MTX-E12 cells were used at passage numbers 52-70 for all experiments. Cells were cultured in DMEM containing 10% FBS, 1% NEAA and 1% penicillin-streptomycin and maintained at 37°C in a 5% CO 2 -humidified air atmosphere and subcultured every 2 days to 3 days similar to the study of Abdelkhaliq et al [26]. For permeability experiments, cells were seeded at a density of 40,000 cells/cm 2 on a polycarbonate Transwell insert (area 0.6 cm 2 , 0.4 μm pore size; Millipore) as follows: Caco-2 and HT29-MTX-E12 cells were seeded in a 3:1 ratio on the apical side of the Transwell system and allowed to attach for 24 h. After 24 h, cell culture medium was refreshed every 2-3 days and Transwell systems were used for permeability experiments following 21 days of culturing.…”
Section: Cell Culturingmentioning
confidence: 99%